2020
DOI: 10.1016/j.pathol.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of SARS-CoV-2 point-of-care antibody tests

Abstract: The aim of this study was to assess the analytic and clinical performance of four rapid lateral flow point-of-care tests (POCTs) for identifying SARS-CoV-2-specific antibodies. A retrospective study was conducted between 22 January and 30 March 2020 on 132 serum samples for SARS-CoV-2-specific antibody detection referred to a tertiary referral hospital laboratory in New South Wales. Multiple sera were tested from 20 confirmed or suspected COVID-19 patients with SARS-CoV-2-specific antibodies detected by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…15,16 On the other hand, they might be infected with SARS-CoV-2 but were not recognized by the rapid IgM/IgG detection system used in the study due to limited sensitivity. 17,18 On the other hand, the asymptomatic human subjects who were IgM and/or IgG positive may refer to the capacity of some of the immune responses in some individuals to clear the infection without developing symptoms, which supports the concept of using convalescent plasma from recovered individuals to passively protect against, or treat, SARS-CoV-2-infected patients. 19,20 In agreement with the recorded asymptomatic antibody-positive individuals in the present work, a study in Iran demonstrated that seroprevalence is likely to be much higher than the reported prevalence of COVID-19 based on confirmed cases.…”
mentioning
confidence: 87%
“…15,16 On the other hand, they might be infected with SARS-CoV-2 but were not recognized by the rapid IgM/IgG detection system used in the study due to limited sensitivity. 17,18 On the other hand, the asymptomatic human subjects who were IgM and/or IgG positive may refer to the capacity of some of the immune responses in some individuals to clear the infection without developing symptoms, which supports the concept of using convalescent plasma from recovered individuals to passively protect against, or treat, SARS-CoV-2-infected patients. 19,20 In agreement with the recorded asymptomatic antibody-positive individuals in the present work, a study in Iran demonstrated that seroprevalence is likely to be much higher than the reported prevalence of COVID-19 based on confirmed cases.…”
mentioning
confidence: 87%
“…However, there is experimental evidence that LFTs are less sensitive at detecting Sars-CoV-2 when compared to the gold-standard RT-PCR tests 52 prompting concerns that false negative tests could seed subsequent outbreaks of Covid-19. 53,54 Despite these misgivings, LFTs have practical advantages in that they can deliver results within two hours of the sample being taken. Furthermore, LFTs are amenable to high throughput and more frequent testing, which renders this method more feasible for large-scale community-level surveillance of infection levels, especially when conducted on a twice weekly basis with the availability of follow-up RT-PCR confirmation when a positive-test is detected.…”
Section: The Pandemic On Campus-physical Health Impacts and Epidemiologymentioning
confidence: 99%
“…This scheme was subsequently expanded into a national mass asymptomatic testing programme for educational settings overseen by the National Health Service test and trace organisation. However, there is experimental evidence that LFTs are less sensitive at detecting Sars‐CoV‐2 when compared to the gold‐standard RT‐PCR tests 52 prompting concerns that false negative tests could seed subsequent outbreaks of Covid‐19 53,54 . Despite these misgivings, LFTs have practical advantages in that they can deliver results within two hours of the sample being taken.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy evaluation estimated the clinical sensitivity to be 97.69%, and clinical specificity to be 100%, with a sample size of 230 positive and 100 negative samples, with the result previously confirmed using SARS-CoV-2 RT-PCR assays. Previous studies evaluating the clinical efficiency of antibody tests used a limited number of confirmed infected samples as well as negative samples [ 16 , 17 ]. These tests were reported to have a low clinical sensitivity from 45% to 65%, with a clinical specificity between 87.3% and 100% [ 16 ], in contrast to the higher sensitivity and specificity of the current study.…”
Section: Discussionmentioning
confidence: 99%